THE FUNCTION OF FUNERAL RITES FOR THE GRIEF PROCESS IN FAMILIES OF BRAZILIANS DEAD BY COVID-19: A SYSTEMATIC REVIEW - Gomes de Araújo Valadares, Weslley; de Souza Silva, Beatriz; Mendes Ferreira, Kátia; Magalhães Neves, Lilyane; Souza dos Santos, Quezia (Health and Society, 2023)
Objective: The aim of this study was to carry out a systematic literature review in order to analyze the function of funeral rites for the mourning process during the COVID-19 pandemic, and to identify the possible psychic reverberations that may occur in the face of this impediment. Methods: Search research in several electronic databases, selecting studies that supported the research objective. Epidemiological studies, observational type, case studies, experience reports, essays, documentary research, and studies that reached a minimum score of 10 points according to the methodological criteria proposed by Downs & Black were included. Results: the studies showed that the suspension of the traditional funeral rite significantly interfered in the elaboration of mourning, which reverberated in psychic illnesses and complicated mourning. Conclusion: The recognition of the importance of carrying out the funeral rite is essential for us to think about the role it plays in the elaboration of mourning. This systematic literature review aimed to understand what possible psychic reverberations could occur in the face of the impossibility of carrying out the funeral rite, as well as to inspire psychology students and other health professionals to deepen their studies in relation to the theme.